Optimalisasi pemberdayaan kader lansia dalam deteksi dini dan perawatan demensia melalui aplikasi digital - Gunawan Irianto; Fuadah Fahrudiana; Prilian Ayu Minarni (JOURNAL of Public Health Concerns, 2026)
Background: Old age (the elderly phase) is a stage in the human life cycle characterized by biological, psychological, and social aging processes. As they age, the elderly are susceptible to various declines in physiological organ function including the central nervous system which impact cognitive function. There has been a sharp rise in the prevalence of degenerative health issues, particularly cognitive impairment and dementia. Addressing this phenomenon requires the vital and strategic role of elderly care volunteers (*kader*). Current health promotion trends position these volunteers not merely as data recorders, but as key facilitators and frontline agents through task shifting in preventive efforts, early detection, and providing support to the families of the elderly within the community. Purpose: To empower volunteers by enhancing their knowledge and technical skills utilizing digital applications regarding early detection and dementia care. Method: The activity was conducted in Kuto Arjo Village, Pesawaran Regency, in collaboration with the KENARI Elderly Family Development Group partner. It involved 10 health volunteers designated for elderly care from the partner organization. The initiative employed an applied and participatory community empowerment approach. The goal was to transfer knowledge and train volunteers in technical skills, specifically the use of digital application-based early detection tools and gamified cognitive training. Volunteers' knowledge levels were measured using pre- and post-educational activity questionnaires. Descriptive assessment was carried out through direct observation as volunteers simulated the use of the application and demonstrated their ability to guide elderly participants through the simulations. Program evaluation involved comparing pretest and posttest scores to assess improvements in the volunteers' knowledge and skills (psychomotor), as well as their achievements throughout the activity. Results: The findings showed an increase in the cadres' average knowledge score from 82.5 points at the pretest to 97.8 points at the posttest. Furthermore, the cadres demonstrated the ability to independently use the early detection application and correctly administer cognitive stimulation across four key domains: visual memory, daily problem-solving, spatial-motor skills, and language. Conclusion: There was a significant improvement in the understanding and knowledge of Integrated Service Post for the Elderly cadres regarding concepts of elderly cognitive health, the distinction between normal aging and pathological dementia, and the importance of early screening and detection starting at the mild cognitive impairment stage. This community service initiative also resulted in tangible improvements in technical skills, enabling cadres to independently demonstrate and operate the digital application for early dementia detection. Suggestion: It is recommended that local community health centers and village authorities sustainably integrate this digital cognitive screening and stimulation program into the routine monthly services of the Integrated Service Post for the Elderly. Keywords: Dementia; Digital application; Early detection; Elderly care cadres; Gamification Pendahuluan: Lanjut usia (lansia) adalah fase perkembangan siklus kehidupan manusia yang ditandai dengan proses penuaan biologis, psikologis, dan sosial. Seiring bertambahnya usia, lansia rentan mengalami berbagai kemunduran fungsi organ fisiologis, termasuk sistem saraf pusat yang berdampak pada penurunan fungsi kognitif . Prevalensi masalah kesehatan degeneratif, khususnya gangguan kognitif dan demensia, mengalami peningkatan tajam. Dalam upaya mengatasi fenomena ini, peran kader lansia menjadi sangat vital dan strategis. Tren promosi kesehatan terkini menempatkan kader tidak hanya sebagai pencatat data, melainkan sebagai fasilitator utama dan ujung tombak (task shifting) dalam upaya preventif, pendeteksian dini, serta pendampingan keluarga lansia di masyarakat Tujuan: Upaya pemberdayaan kader dengan meningkatkan pengetahuan dan keterampilan teknis berbasis aplikasi digital dalam deteksi dini dan perawatan demensia. Metode: Kegiatan dilaksanakan di Desa Kuto Arjo, Kabupaten Pesawaran bersama mitra Kelompok Bina Keluarga Lansia (BKL) KENARI. Melibatkan 10 kader kesehatan yang merupakan kader lansia dari mitra. Kegiatan dilakukan dengan pendekatan pemberdayaan masyarakat (community empowerment) yang bersifat aplikatif dan partisipatif. Sasaran dalam kegiatan ini adalah memberikan transfer pengetahuan, melatih keterampilan teknis kader dalam menggunakan instrumen deteksi dini berbasis aplikasi digital dan cognitive training gamifikasi. Pengukuran parameter tingkat pengetahuan kader menggunakan kuesioner yang diberikan sebelum kegiatan (pretest) dan sesudah kegiatan edukasi (posttest). Penilaian deskriptif melalui observasi langsung saat kader mensimulasikan penggunaan aplikasi dan kemampuannya mendampingi simulasi lansia. Evaluasi pelaksanaan program dilakukan dengan membandingkan hasil skor pretest dan posttest untuk melihat peningkatan pengetahuan dan keterampilan (psikomotorik) kader serta hasil pencapaian selama mengikuti kegiatan. Hasil: Menunjukkan adanya peningkatan rata-rata nilai pengetahuan kader dari 82.5 poin pada saat pretest menjadi 97.8 poin pada saat posttest. Selain itu, kader terbukti mampu mendemonstrasikan secara mandiri penggunaan aplikasi deteksi dini dan melakukan stimulasi kognitif secara tepat pada empat aspek utama, yaitu memori visual, pemecahan masalah harian, spasial-motorik, dan bahasa. Simpulan: Terdapat peningkatan pemahaman dan pengetahuan yang signifikan pada kader Posyandu Lansia mengenai konsep kesehatan kognitif lansia, perbedaan antara penuaan normal dan demensia patologis, serta pentingnya melakukan skrining/deteksi dini sejak fase gangguan kognitif ringan (mild cognitive impairment). Kegiatan pengabdian ini juga memberikan peningkatan keterampilan teknis yang nyata, di mana kader mampu mendemonstrasikan dan mengoperasikan aplikasi digital untuk pendeteksian dini demensia secara mandiri. Saran: Diharapkan puskesmas dan perangkat desa setempat dapat secara berkelanjutan mengintegrasikan program skrining dan stimulasi kognitif digital ini ke dalam layanan rutin bulanan Posyandu Lansia.